One‐Step Synthesis of Acylboron Compounds via Copper‐Catalyzed Carbonylative Borylation of Alkyl Halides - Cheng, Li‐Jie; Zhao, Siling; Mankad, Neal P. (Angewandte Chemie International Edition, 2021)
A copper‐catalyzed carbonylative borylation of unactivated alkyl halides has been developed, enabling efficient synthesis of aliphatic potassium acyltrifluoroborates (KATs) in high yields by treating the in situ formed tetracoordinated acylboron intermediates with aqueous KHF2. A variety of functional groups are tolerated under the mild reaction conditions, and primary, secondary, and tertiary alkyl halides are all applicable. In addition, this method also provides facile access to N‐methyliminodiacetyl (MIDA) acylboronates as well as α‐methylated potassium acyltrifluoroborates in a one‐pot manner. Mechanistic studies indicate a radical atom transfer carbonylation (ATC) mechanism to form acyl halide intermediates that are subsequently borylated by (NHC)CuBpin. A copper‐catalyzed carbonylative borylation of unactivated alkyl halides enables one‐step synthesis of acylborons which can be further transformed into potassium acyltrifluoroborates (KATs) as well as N‐methyliminodiacetyl (MIDA) acylboronate in a one‐pot manner.